The Role of Gravity Wave Drag Optimization in the Splitting of the Antarctic Vortex in the 2002 Sudden Stratospheric Warming - Scheffler, Guillermo Federico (2018)
The impact of gravity wave drag on the Antarctic sudden stratospheric warming (SSW) in 2002 is examined through a mechanistic middle atmosphere model combined with a variational data assimilation system. Significant differences in the SSW representation are found between a model integration that uses reference gravity wave parameters and one that uses parameters estimated using data assimilation. Upon identical wave forcings at 100 hPa, the vortex breakdown may arise as either a vortex splitting event or a displacement vortex event depending on gravity wave parameters. A local enhancement of Rossby waves is found in the integration with estimated parameters, leading to a split SSW. The changes in the vortex breakdown are associated with changes in the vortex geometry caused entirely by modifying the gravity wave parameters. Gravity wave drag proved to play an instrumental role in preconditioning the stratosphere near a resonant excitation point that triggers the split SSW.